KETELADANAN KHULAFAURRASYIDIN DALAM PROSES PEMBENTUKAN KARAKTER MUSLIM: STUDI ANALISIS PADA PEMBELAJARAN AQIDAH AKHLAK MADRASAH TSANAWIYAH - Laili, Rahmatul; Adona, Putri; Haida Rahma, Rifka; saputra, indra (STAI Darul Quran Payakumbuh, 2024)
Khulafaurrasyidin's exemplary and positive values ​​are very important in developing Muslim character. Khulafaurrasyidin's exemplary has become a reference or source for Muslims in developing good character and behavior according to Islamic teachings. For this reason, in this research the author wants to analyze material about Khulafaurrasydin's exemplary in learning Aqidah Akhlak at Madrasah Tsanawiyah. The research method used is a qualitative method with a content analysis approach by understanding and studying theory and various literature related to the research. After conducting an in-depth analysis, the author found that the structure of the Aqidah Akhlak material at Islamic Junior High School has quite extensive discussion. So in this discussion the author discusses two subthemes, these two subthemes are 1). The exemplary of Khalifa Abu Bakar Ash-Siddiq. 2). The exemplary of KhalifaUmar bin Khattab. In the future, the author hopes that this research will have a positive impact, especially in madrasas as formal educational institutions with the characteristic of instilling Islamic values ​​in their students.